2020
DOI: 10.6007/ijarbss/v10-i14/7367
|View full text |Cite
|
Sign up to set email alerts
|

ARTIQUE: An Art Criticism Session through Online Gallery for Independent Artists

Abstract: Studio critiquing that is generally carried out in physical sites should be done at virtual and beyond offline platforms in order to overcome geographic boundaries amongst professional artists, fellow students, galleries and museums. This research reports on a study of the impact of art criticism in an online gallery for independent artists. The main objective is to observe independent artists' development. An online gallery was created by utilizing design and development research (DDR) by Richey and Klein (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…The communication that occurs in SNS sited could build and shape educational goals and while simultaneously encouraging individual communication (Kord, 2008). Maaruf, et al's (2020) study demonstrated the advantages of having an online gallery for art criticism for independent artists, students, and art collectors.…”
Section: Discussionmentioning
confidence: 86%
“…The communication that occurs in SNS sited could build and shape educational goals and while simultaneously encouraging individual communication (Kord, 2008). Maaruf, et al's (2020) study demonstrated the advantages of having an online gallery for art criticism for independent artists, students, and art collectors.…”
Section: Discussionmentioning
confidence: 86%